1999
DOI: 10.1021/bi9904151
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Rabbit Cytosolic Serine Hydroxymethyltransferase at 2.8 Å Resolution:  Mechanistic Implications,

Abstract: Serine hydroxymethyltransferase (SHMT) catalyzes the reversible cleavage of serine to form glycine and single carbon groups that are essential for many biosynthetic pathways. SHMT requires both pyridoxal phosphate (PLP) and tetrahydropteroylpolyglutamate (H4PteGlun) as cofactors, the latter as a carrier of the single carbon group. We describe here the crystal structure at 2.8 A resolution of rabbit cytosolic SHMT (rcSHMT) in two forms: one with the PLP covalently bound as an aldimine to the Nepsilon-amino grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
104
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(110 citation statements)
references
References 49 publications
6
104
0
Order By: Relevance
“…This was confirmed by the modelling studies of hcSHMT and rabbit liver cytosolic SHMT [3,4]. A detailed study of the catalytic mechanism of SHMT revealed that the addition of substrate, serine\glycine, generates an external aldimine that undergoes deprotonation at the α-carbon atom to form the quinonoid intermediate.…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…This was confirmed by the modelling studies of hcSHMT and rabbit liver cytosolic SHMT [3,4]. A detailed study of the catalytic mechanism of SHMT revealed that the addition of substrate, serine\glycine, generates an external aldimine that undergoes deprotonation at the α-carbon atom to form the quinonoid intermediate.…”
Section: Introductionmentioning
confidence: 63%
“…This alteration in reaction and\or substrate specificity of an enzyme is brought about by subtle changes in local conformations around the active site owing to changes in the primary structure of the proteins. As mentioned previously, although the active-site geometries of AATase and mammalian SHMT are quite similar [3,4], they catalyse different physiological reactions. AATase uses dicarboxylic amino acids as substrates and catalyses transamination, whereas SHMT is more efficient with monocarboxylic acids and transfers the hydroxymethyl group of serine to H % -folate [11].…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations